Zinc oxide nanoparticles improve lettuce (Lactuca sativa L.) plant tolerance to cadmium by stimulating antioxidant defense, enhancing lignin content and reducing the metal accumulation and translocation - Gao, Feng; Zhang, Xiaodan; Zhang, Jing; Li, Jing; Niu, Tianhang; Tang, Chaonan; Wang, Cheng; Xie, Jianming (Frontiers in Plant Science, 2022)
Cadmium (Cd) contamination is a serious global concern that warrants constant attention. Therefore, a hydroponic study was conducted to evaluate the effect of different concentrations (0, 1, 2.5, 5, 10, 15 mg/l) of zinc oxide nanoparticles (ZnONPs) on the Cd content in lettuce (Lactuca sativa L.) under Cd stress conditions. The results showed that Cd stress triggered a decrease in plant biomass, an increase in relative electrolyte conductivity (REC), a decrease in root activity, accumulation of reactive oxygen species (ROS) accumulation, and nutrient imbalance. The application of ZnONPs reduced the toxicity symptoms of lettuce seedlings under Cd stress, with the most pronounced effect being observed 2.5 mg/l. ZnONPs promoted the growth of lettuce under Cd stress, mainly in terms of increase in biomass, chlorophyll content, antioxidant enzyme activity, and proline content, as well as reduction in Cd content, malondialdehyde, and reactive oxygen species (ROS) in plant tissues. ZnONPs also enhanced the uptake of ions associated with photosynthesis, such as iron, manganese, magnesium, and zinc. In addition, ZnONPs increase the amount of lignin in the roots, which blocks or reduces the entry of Cd into plant tissues.